Rattus timorensis Kitchener, Aplin, and Boeadi 1991 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus timorensis Kitchener, Aplin, and Boeadi, 1991. Rec. West. Aust. Mus., 15:446. TYPE LOCALITY: Indonesia, Nusa Tenggara, Timor, Gunung Mutis, 1900 m, 7 km E Desa Nenas. DISTRIBUTION: Known only from the type locality. COMMENTS: Represented only by the holotype. Some of the large series of subfossil fragments collected in E Timor by Glover (1986) may be this species. Phylogenetic affinities unknown, and possibly not even a member of Rattus (Kitchener et al., 1991 b). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 661, DOI: 10.5281/zenodo.7353098